Organizational Culture in Realizing Higher Education Innovation in Private Universities in Jambi Province - Mawaddah Warahmah; Kaspul Anwar Us; Badarusyamsi, Badarusyamsi (Yayasan pendidikan dzurriyatul Quran, 2025)
The rapid transformation of the higher education landscape demands that universities develop adaptive and innovative organizational cultures to remain competitive and sustainable. This study aims to analyze the role of organizational culture in fostering innovation within private Islamic higher education institutions in Jambi Province. A qualitative approach with a case study design was employed, involving three institutions: IAI Muhammad Azim, IAI Yasni Muaro Bungo, and Nusantara Batanghari University. Data were collected through observation, in-depth interviews, and documentation, and then analyzed descriptively. The findings reveal that a strong organizational culture characterized by effective communication, team collaboration, visionary leadership, and the integration of Islamic values significantly contributes to academic, managerial, and social innovation within universities. However, challenges such as limited human resources, inadequate facilities, and insufficient funding remain. The implications highlight the importance of systematically strengthening organizational culture as a foundation for sustainable innovation and institutional development in Islamic higher education